Common single-base insertions in the VNTR of the carboxyl ester lipase (CEL) gene are benign and also likely to arise somatically in the exocrine pancreas - Brekke, Ranveig S; Gravdal, Anny; El Jellas, Khadija; Curry, Grace E; Lin, Jianguo; Wilhelm, Steven J; Steine, Solrun J; Mas, Eric; Johansson, Stefan; Lowe, Mark E; Johansson, Bente B; Xiao, Xunjun; et al. (Human molecular genetics, 2024)
The CEL gene encodes carboxyl ester lipase, a pancreatic digestive enzyme. CEL is extremely polymorphic due to a variable number tandem repeat (VNTR) located in the last exon. Single-base deletions within this VNTR cause the inherited disorder MODY8, whereas little is known about VNTR single-base insertions in pancreatic disease. We therefore mapped CEL insertion variants (CEL-INS) in 200 Norwegian patients with pancreatic neoplastic disorders. Twenty-eight samples (14.0%) carried CEL-INS alleles. Most common were insertions in repeat 9 (9.5%), which always associated with a VNTR length of 13 repeats. The combined INS allele frequency (0.078) was similar to that observed in a control material of 416 subjects (0.075). We performed functional testing in HEK293T cells of a set of CEL-INS variants, in which the insertion site varied from the first to the 12th VNTR repeat. Lipase activity showed little difference among the variants. However, CEL-INS variants with insertions occurring in the most proximal repeats led to protein aggregation and endoplasmic reticulum stress, which upregulated the unfolded protein response. Moreover, by using a CEL-INS-specific antibody, we observed patchy signals in pancreatic tissue from humans without any CEL-INS variant in the germline. Similar pancreatic staining was seen in knock-in mice expressing the most common human CEL VNTR with 16 repeats. CEL-INS proteins may therefore be constantly produced from somatic events in the normal pancreatic parenchyma. This observation along with the high population frequency of CEL-INS alleles strongly suggests that these variants are benign, with a possible exception for insertions in VNTR repeats 1–4.